Dermal exposure of Eisenia andrei earthworms: Effects of heavy metals on metallothionein and phytochelatin synthase gene expressions in coelomocytes. (28th April 2015) - Homa, Joanna; Rorat, Agnieszka; Kruk, Jerzy; Cocquerelle, Claude; Plytycz, Barbara; Vandenbulcke, Franck
Abstract Parameters such as total number of coelomocytes, riboflavin content in coelomocytes, expression of genes implied in metal homeostasis, and detoxification mechanisms can be used as biomarkers to assess the impact of metals on annelids. Defense biomarkers (detoxification gene expressions and coelomocyte parameters) were investigated in the ecotoxicologically important species Eisenia andrei following in vivo exposure to 5 different metals (zinc, copper, nickel, lead, and cadmium) at known concentrations. Coelomocyte numbers and riboflavin content were not affected by metallic exposure, but metal‐specific gene expression variations were evidenced. Environ Toxicol Chem 2015;34:1397–1404. © 2015 SETAC